Predictors Associated With Increased Prevalence of Abdominal Aortic Aneurysm in Chinese Patients with Atherosclerotic Risk Factors. (July 2017) - Li, W.; Luo, S.; Luo, J.; Liu, Y.; Ning, B.; Huang, W.; Xue, L.; Chen, J.
Abstract : Objective/Background: Epidemiological screening studies have demonstrated that the prevalence of abdominal aortic aneurysm (AAA) of Asian origin appears to be low and so increases uncertainty about the cost effectiveness of screening for AAAs in Chinese people. Some studies have demonstrated a higher prevalence of AAA in patients with atherosclerotic risk factors. The purpose of the study was to determine the prevalence of AAA and to explore the high risk group of AAA in Chinese patients with atherosclerotic risk factors. Methods: From November 2014 to July 2015, a prospective observational study was conducted in Guangdong General Hospital. In total, 1582 consecutive patients with atherosclerotic risk factors and undergoing coronary angiography for suspected or known coronary artery disease were enrolled to be screened for AAA by abdominal aortic ultrasound. Because of inadequate ultrasound image quality, the analysis was based on the 1541 (97.4%) patients whose abdominal aortic ultrasound images were adequate. Results: The prevalence of AAA was 1.6% in the whole study population and 2.9% in male patients aged over 65 years. In multivariate analysis, age ≥ 65 years ( p = .029), smoking ( p = .037), hypertension ( p = .026), and aortic root diameter > 30 mm ( p = .003) were independent predictors of AAA. The prevalence of AAA was 0% (0/153) in patients without any independent predictor, 0.6% (3/502) in patients with one predictor, 1.0% (6/597) in patients with two predictors, 4.8% (12/249) in patients with three predictors, and up to 10% (4/40) in patients with four predictors ( p < .001; p value for trend < .001). Conclusion: Age ≥ 65 years, smoking, hypertension, and aortic root diameter > 30 mm emerged as independent predictors of AAA in Chinese patients. Stepwise increases in the prevalence of AAA were found to depend on the number of independent predictors. Ultrasound screening for AAA could be considered in these high risk patients, especially those with three or four predictors.